Comparison Of Chemical Profiles Of Black Cumin Seed (Nigella Sativa .L) Extracts And Evaluation Of Their Cytotoxic Effect On Breast Cancer Mcf-7 And Mda-Mb- 231 Cell Lines - Ghahramanloo, Kourosh Hasanzadeh (2009)

(untitled)
Breast cancer is one of the main life-threatening diseases that a woman may have to face during her lifetime. This study was proposed in order to investigate the anticancer effects of the active ingredients of Nigella sativa crude extract, Thymoquinone (TQ), and Linoleic Acid (LA) on breast cancer MCF-7 and MDAMB- 231 cell lines. According to study design of this research, the study was performed in two parts respectively: 1. Extraction and Identification of Nigella sativa composition The main objective of this part of the present study was to compare the extract and oil composition of Iranian and Indian Nigella sativa L. extracted, using Super Critical Fluid Extraction (SFE) and solvent extraction.